Distribution and Isotopic Composition of Living Planktonic Foraminifera N. pachyderma (sinistral) and T. quinqueloba in the High Latitude North Atlantic. - Stangeew, Elena (2001)
With the examination of multinet catches (63 µm mesh size), the present study analyzes the distribution of planktonic foraminifera in Polar regions: the Labrador Sea, Greenland Sea at 75°N and Fram Strait at 80°N. The community of the planktonic foraminifera, which in the study area mainly consists of six species: left and right-coiling N. pachyderma, T. quinqueloba, G. bulloides, G. glutinata and G. uvula, is primarily controlled by the temperature in the different water masses. Besides hydrographic parameters, the changes in the horizontal and vertical distribution of N. pachyderma (s.) and T. quinqueloba as well as their shell size distribution in the study area are primarily influenced by the synchrone reproduction, which is coupled to the lunar cycle. Detailed examinations of the isotope signal in dependency on the shell size and weight for N. pachyderma (s.) and T. quinqueloba from plankton tows, indicated the weight or degree of calcification to not be the primary factor controlling the isotope signal of encrusted specimens.The d18O vital effect is primarily caused by the thermal stratification of the water column, whereas the d13C vital effect mainly results from the ontogenetic development.